Beckman microcircuits with cigarette - Hesketh, Dean D. (1964)
This photograph is part of a series of marketing images used to demonstrate the small size of Helipot products, in this case microcircuits.
Keywords: Microelectronics; Ashtrays; Cigarettes; Beckman Instruments, Inc.